Causal relationship between cheese intake and risk of gastroesophageal reflux disease and Barrett's esophagus: findings from multivariable mendelian randomization and mediation analysis. - Zhou, Jianfeng; Fang, Pinhao; Liu, Yixin; Liang, Zhiwen; Luan, Siyuan; Xiao, Xin; Li, Xiaokun; Shang, Qixin; Zhang, Hanlu; Zeng, Xiaoxi; Yang, Yushang; Yuan, Yong (European Journal of Nutrition, 2025)
Objective: Previous studies have indicated a potential correlation between cheese intake and risk of various diseases. However, establishing a causal relationship is challenging. To address this, we employed Mendelian randomization (MR) to simulate randomized trial groups and to investigate whether there is a causal link between cheese intake and the risk of gastroesophageal reflux disease (GERD) and Barrett's esophagus. Methods: We conducted a multivariable MR analysis using individual-level data on GERD and Barrett's esophagus from the published datasets. Univariable and multivariable MR investigations were carried out to explore and substantiate the causal association between genetically predicted cheese intake and esophageal diseases. Additionally, a network MR analysis was executed to identify potential intermediate variables. Results: Based on the primary causal effects model using MR analyses with the inverse-variance weighted (IVW) method, the genetically predicted that cheese intake demonstrated a protective factor of GERD (OR = 0.356; 95% CI 0.256–0.495; P = 8.22E-10) and Barrett's esophagus (OR = 0.223; 95% CI 0.114–0.437; P = 1.19E-5). These effects remained consistent after adjusting for potential confounders such as tobacco smoking (GERD: OR = 0.440; 95% CI 0.347 − 0.558; P = 1.17E-11; Barrett's esophagus: OR = 0.263; 95% CI 0.160 − 0.432; P = 1.33E-7) and BMI (GERD: OR = 0.515; 95% CI 0.424 − 0.626; P = 2.49E-11; Barrett's esophagus: OR = 0.402; 95% CI 0.243 − 0.664; P = 3.72E-4). Furthermore, the network MR showed that BMI mediated 28.10% and 27.50% of the causal effect of cheese intake on GERD and Barrett's esophagus, respectively, with statistically significant mediation effects. Conclusion: The multivariable MR analysis conducted in this study revealed a reverse causal relationship between cheese intake and GERD and Barrett's esophagus. Furthermore, BMI was potential mediating factor of the cheese intake effects on GERD and Barrett's esophagus. This finding provides causal evidence for the potential protective role of cheese intake in the prevention of esophageal diseases. The mediating effect of BMI suggests that dietary interventions combined with weight management may help reduce the risk of these diseases.